Innovative Perspectives on Interactive Communication Systems and Technologies - Sarfraz, Muhammad (IGI Global, 2020)
Digital communication has become increasingly prominent in numerous disciplines throughout society due to the high usage levels of interactive systems. Professionals continue to apply trending technologies to their traditional practices as social interaction becomes more computerized. As new innovations are continually being discovered, researchers and practitioners in various areas of work need to stay up to date on the latest findings within interactive communication systems. Innovative Perspectives on Interactive Communication Systems and Technologies is a collection of innovative research.